STUDIES ON THE FREEZABILITY OF KUNDHI BUFFALO BULL SEMEN - Z. U. Rehman; M. U. Samo; T. A. Qureshi; S. Khan; M. S. Qureshi; F. A. Khan; S. Bahadadr (Journal of Animal and Plant Sciences, 2012)
This study was conducted to assess the post thaw quality of Kundhi buffalo semen diluted in tris based diluents. After collection the ejaculates were pooled and checked for color, volume, pH, mass activity, progressive linear motility%(PLM), and intactness of cell membrane. The semen qualifying these tests was divided into four aliquots A, B, C and D, diluted with tris based diluents; the last three diluents containing sugar types glucose, fructose and lactose respectively. Aliquot A was without sugar and severed as control. These were frozen, stored for 24 hrs, thawed and incubated at 350C for 5 hrs. The incubated semen aliquots were examined for PLM and membrane integrity of sperm cells with phase- contrast microscopy and HOST procedures. It was observed that all the ejaculates were creamy white in color. The mean (±SEM) volume, mass activity, sperm concentration, PLM, and intactness of cell membrane were 1.70 (±0.09) ml, 3.22 (±0.074), 1.58 (±0.136) x 109 /ml, 64.53 (±0.757) % and 55.63 (±0.945)% respectively for fresh semen. A significant difference was observed in pH values of the fresh semen samples among the bulls. There was a significant decrease in the number of motile cells and the cells with intact membrane after thawing and incubation of the semen at 350C. Addition of fructose in the diluents was found to be superior in maintaining higher PLM and intactness of membrane after thawing and incubation. The objective method, Osmotic resistance test (ORT) was found to be the useful parameter for assessment of in-vitro fertility of Kundhi buffalo bull semen.
Keywords: Semen Freezing; Sperm membrane integrity; Progressive linear motility; Kundhi buffalo